Prognostic models for predicting recurrence and survival in women with endometrial cancer - Wan, Y Louise (Cochrane Database Syst Rev, 2021)
This is a protocol for a Cochrane Review (prognosis). The objectives are as follows: To review all prognostic models that combine two or more clinical, histological or molecular variables, or a combination of these variables, to provide an individualised assessment of risk of recurrence or death from disease and evaluate their performance to predict these outcomes in people undergoing curative treatment for endometrial cancer.